Mild Encephalitis/Encephalopathy with Reversible Splenial Lesion (MERS) due to Cytomegalovirus: Case Report and Review of the Literature - Feraco, Paola; Porretti, Giulia; Marchiò, Giuliana; Bellizzi, Maria; Recla, Mauro (Neuropediatrics, 2018)
Mild encephalopathy with a reversible splenial lesion (MERS) is a clinico-radiological syndrome characterized by a transient mild encephalopathy and MRI findings of a reversible lesion in the splenium of corpus callosum (SCC). It is classified in MERS type I and MERS type II, depending on the involvement of SCC alone or also other white matter areas. The syndrome mainly affects children and young adults; the prognosis is favorable with complete or nearly complete neurological and radiological resolution within days or weeks. The vast majority of the cases described in the literature involve Asian and Australian children. The exact pathophysiology is unknown; however, infectious-related MERS (in particular virus associated MERS) remains the most common cause of reversible splenial lesions in childhood. To the best of our knowledge, there is only one published case of MERS associated with cytomegalovirus (CMV) infection involving an Australian child. We present here the first case of a CMV-related MERS in a European Caucasian child.
Keywords: MERS; CMV; splenial reversible lesion